PENGEMBANGAN MULTIMEDIA PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN RENDERFOREST BERBASIS MODEL PROBELM BASED LEARNING DI STKIP MUHAMMADIYAH KALABAHI - Amsidi, Mukmin; Suparman, Suparman (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2023)
The demands of the learning process must be interesting, so new innovations are needed. Education is currently in the midst of the COVID-19 pandemic, so one of the alternatives that the government currently uses in the learning process is online and offline learning, or what we usually call blended learning. Many people think of mathematics as a difficult subject to learn. The purpose of this research is to create interesting learning media using applications and use learning videos to arouse students' interest in learning mathematics. The research approach used in this study is R&D and the ADDIE product development model. First year students from the Mathematics Education Study Program of STKIP Muhammadiyah Kalabahi are the subjects of this learning video. Questionnaires and working papers were used to collect data. The results shows that the validity is successful in terms of media and material validation as well as student responses. The learning videos can already be used by teachers when the teaching and learning process is carried out through a problem-based model.